Tunable Green Emitting Novel Phosphazene Compounds via Azide-Alkyne Cycloaddition: Evaluation of Photodiode Performance, Synthesis, and Photophysical Characterization - Seker, Ferhan Sultan; Cetiner, Rumeysa; Kane, Labouda; Akman, Feride; Biryan, Fatih; Caliskan, Eray; Koran, Kenan (Amer Chemical Soc, 2026)
This study aims to develop new photodiode materials containing functional chalcone derivatives by combining the electronic properties of the cyclotriphosphazene ring with click chemistry. Azide-terminated chalcones were subjected to a click reaction with an alkyne-functionalized dispirocylotriphosphazene (Bif-PA) to afford the Bif-PA-Click-Chal 1-4 compounds, whose structural characterizations were confirmed by FT-IR, NMR, and MALDI-TOF MS analyses. Photophysical properties were investigated using UV-vis and fluorescence spectroscopy, and the Bif-PA-Click-Chal 1 compound exhibited a quantum yield of 0.32 and high emission intensity. For the Bif-PA-Click-Chal 1 molecule, absorption parameters were calculated using CPCM/6-31G(d,p) and TD-DFT/CAM-B3LYP methods (in THF), revealing a theoretical bandgap of 3.53 eV, whereas experimental UV-vis measurements indicated a bandgap of 2.69 eV. Electrical measurements were performed to investigate the I-V characteristics of the new types of diodes fabricated using the Bif-PA-Click-Chal 1-4 compounds. Among these, Bif-PA-Click-Chal 1 and 2 demonstrated diode performance. Comparison of their diode properties showed that both compounds behaved as semiconductors exhibiting diode characteristics. Bif-PA-Click-Chal 2 stood out with a high rectification ratio (RR = 523.64), low saturation current (I 0 = 1.27 x 10-8 A), a better ideality factor (n = 2.51), and high barrier height (phi b = 0.76 eV). However, measurements performed under various light intensities indicated that it did not exhibit photodiode behavior. In contrast, Bif-PA-Click-Chal 1, despite displaying a lower rectification ratio (RR = 80.45), higher saturation current (I 0 = 2.38 x 10-8 A), and an ideality factor of n = 2.73, demonstrated photodiode behavior under different light intensities. These findings confirm that both compounds exhibit diode characteristics; however, the photodiode behavior of Bif-PA-Click-Chal 1 and its superior I-V characterization reveal that it possesses enhanced electronic and photoconductive properties compared to its counterparts.
Keywords: Dielectric-Properties; Series Resistance; Click Chemistry; Band-Gap; Fluorescence; Diodes; Cyclophosphazenes; Temperature; Fabrication; Dependence